Preterm birth due to cervical insufficiency complicated by placenta accreta and postpartum haemorrhage managed by uterine artery embolisation - Tetere, Elina; Jekabsone, Anna; Kalere, Ieva; Matule, Dace (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
In this report, we present the case of a young woman undergoing her second pregnancy, with early detected shortened cervix resulting in cervical cerclage procedure. At gestational week 24/25, she presented at a hospital with signs of intra-amniotic infection and spontaneous rupture of membranes. This resulted in pathological preterm delivery with massive postpartum bleeding, which was managed by bilateral uterine artery embolization. Reasons for preterm birth and management options are discussed.